Tingkat Pendidikan dan Kualitas Penduduk: Analisis Indeks Pembangunan Manusia di Indonesia - Faty Rahmarisa; Ismail Nasution; M. Tahir (Universitas Islam Sumatera Utara, 2026)
This study aims to analyze the influence of education levels on population quality in Indonesia. Population quality is an important indicator in determining a nation's competitiveness amid the dynamics of global competition. This study employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS) and relevant literature. The analysis focuses on the relationship between education levels, including mean years of schooling, expected years of schooling, and educational participation, and population quality as measured by the Human Development Index (HDI). The results indicate that education levels have a significant influence on improving population quality in Indonesia. Increases in mean years of schooling and expected years of schooling contribute positively to the HDI. However, disparities in access to education between urban and rural areas and across economic groups remain major challenges. Therefore, affirmative policies are needed to expand equitable access to quality education.